Sociology and psychoanalysis of personality in Khaje Nizam al-Mulk's policy - Ahmad Foruozanf, Foruozandeh Edalat Kasha (Opción, 2019)
Nizam al-MulkTusi's textbook is one of the most important works of Persian prose in the fifth century which has been written about the rule of the kingdom and the country. The purpose of this research, which is carried out in a descriptive-analytical manner, is firstly familiarizing with Syr-al-Muluk, and then, by bringing six stories from this book, is answering these questions in simple prose. As conclusion, Anooshirvan, Amir, Alexander, Omran Abdul Aziz Shuja, Delaware and Shah are just, gentler and prospective. They have a kind and altruistic personality whose presence and justice bring peace and relief to others' imagination.